Respiratory health and allergies from chemical exposures among machining industry workers in Selangor, Malaysia - Liaw, Soo Hui; Hashim, Zailina; Lye, Munn Sann; Zainuddin, Huda (Tehran University of Medical Sciences, 2014)
Background: This study was to determine the prevalence of respiratory health complaints, allergy symptom, lung functions, and the association between airborne concentrations of chromium and aluminium with respiratory health and allergy symptoms among machining industry workers in Selangor, Malaysia.